Encyclopedia of comparative iconography : themes depicted in works of art - Roberts, Helene E. (Chicago : Fitzroy Dearborn, 1998)
"Answers to how various mythological, Biblical, and literary themes have been treated in literature, art, music, and the performing arts can be found in this work. It provides an analysis of over 100 selected themes that reflect the increasingly interdisciplinary nature of scholarly and academic work through the use of various iconographical sources. The alphabetical arrangement facilitates browsing, while the six indexes provide multiple access by considering, among others, references to the Bible; Judeo-Christian personages, places and concepts; and artists and works of art".--"Outstanding Reference Sources : the 1999 Selection of New Titles", American Libraries, May 1999. Comp. by the Reference Sources Committee, RUSA, ALA.
v.1. A-L -- v. 2. M-Z.
Includes bibliographical references and indexes.
Keywords: Art -- Themes, motives -- Encyclopedias